Status of corneal endothelial cells in the presence of silicone oil in the anterior chamber - Machiko Shimmura-Tomita (Nature Portfolio, 2021)
Abstract To evaluate corneal endothelium damage with silicone oil (SO) presence in the anterior chamber after pars plana vitrectomy. We investigated the medical records of consecutive 54 eyes of 53 patients undergoing SO removal after pars plana vitrectomy with SO tamponade at Saitama Medical Center, Jichi Medical University, Japan. We recorded SO tamponade retention period, anterior chamber SO with gonioscope, area of SO attachment to the corneal endothelium before SO removal surgery, and the lens status. We then retrospectively investigated the correlation between SO presence in the anterior chamber and the decrease rate of corneal endothelial cell (CEC) density during SO tamponade. The average decrease rate of CEC density was 7.6 (0–38.1) %. The correlation between SO tamponade retention period and decrease rate of CEC density was high (p = 0.0001). However, there was no correlation between anterior chamber SO under gonioscope, SO attaching area, and lens status with the decrease rate of CEC density (p = 0.11, p = 0.93, p = 0.16). No correlation was observed between CEC loss and the existence of anterior chamber SO, although CEC decrease rate was relatively high after a long SO tamponade period. These findings suggest that SO presence in the anterior chamber may not directly injure CEC.